Attitude and Behavior towards Self-medication using Non-steroidal Anti-inflammatory Drugs and Paracetamol among Housewives in Hegarmanah Village, Jatinangor - Kuswinarti Kuswinarti; Aisyah Binti Mohamad Rohim; Siti Aminah (Althea Medical Journal, 2020)
Background: The use of drugs by self-medication is widely practiced worldwide. One of the most common drugs used without prescription is analgesic and this is predominantly used among housewives since they are sometimes suffering from minor ailments due to house chores burden. The study aimed to explore the attitude and behavior of Non-steroidal Anti-inflammatory Drugs (NSAIDs) and paracetamol usage among housewives in Jatinangor, West Java-Indonesia.Methods: A cross-sectional study was performed from August–November 2013. After informed consent, housewives living in Hegarmanah village, Jatinangor were included by filling in a validated questionnaire to assess the level of attitude and behavior of NSAIDs and paracetamol usage. The data were presented in percentages. The score was given and categorized as good, moderate and poor for both attitude and behavior.Results: Of a total 110 housewives participated in this study, the attitude of housewife towards the drug use was good (59.1%), moderate (33.6%) and poor (7.3%), whereas the behavior was good (46.4%), moderate (52.7%) and poor (0.9%).Conclusions: The majority of the respondents have moderate to good attitude as well as behavior toward the usage of NSAIDs and paracetamol as self-medication. Public health education and awareness are important to ensure safe and useful self-medication.